2008
DOI: 10.1007/s12020-008-9116-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased thrombin-activatable fibrinolysis inhibitor and decreased tissue factor pathway inhibitor in patients with hypothyroidism

Abstract: Various abnormalities of coagulation-fibrinolytic system have been reported in patients with thyroid dysfunction. Several studies indicate that coagulation and fibrinolytic system is disturbed in the patients with hypothyroidism. Also, the influence of hypothyroidism on hemostasis is controversial; both hypocoagulable and hypercoagulable states have been reported. The levels of plasma thrombin-activatable fibrinolysis inhibitor (TAFI) antigen and tissue factor pathway inhibitor (TFPI) have been investigated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…Interestingly, we very recently demonstrated a quite similar hypercoagulative status in hypothyroid patients (decreased TFPI and increased TAFI) [43]. A cause of the analogies between the results obtained in the two studies is not clear.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, we very recently demonstrated a quite similar hypercoagulative status in hypothyroid patients (decreased TFPI and increased TAFI) [43]. A cause of the analogies between the results obtained in the two studies is not clear.…”
Section: Discussionmentioning
confidence: 77%
“…TAFI : [45,46] N normal, vWD von Willebrand Disease, TF tissue factor, PT prothrombin time, aPTT activated partial thromboplastin time, : increased, ; decreased, = the change is not significant : increased, ; decreased, = the change is not significant…”
Section: Resultsmentioning
confidence: 99%
“…In two different studies that we have conducted, an increase in fibrinogen, FVII, PAI-1, AT III, TM, and TAFI, and a decrease in FV, FVIII, vWF, protein C, protein S, and TFPI was determined in patients with newly diagnosed and untreated hypothyroidism compared to the control group. As a consequence, it was suggested that these changes might indicate endothelium dysfunction, hypofibrinolysis, and hypercoagulability rather than a tendency toward bleeding; thus, might lead to an increase in the risk for thrombosis [5,46].…”
Section: Coagulation Factorsmentioning
confidence: 99%
“…Most studies have suggested that patients with SCH have abnormal blood lipid levels, which may accelerate atherosclerosis [39-41]. It has also been proposed that the coagulation and fibrinolytic systems are disturbed in patients with SCH [42, 43]. Moreover, patients with SCH tended to exhibit increased platelet activation and platelet activity which enhances the risk of atherothrombosis in CHD [44].…”
Section: Discussionmentioning
confidence: 99%